DETERMINATION OF EXPIRY DATE OF FOOD ADDITIVES OBTAINED FROM SECONDARY RESOURCES OF PEAR PROCESSING - O. V. Fedoseeva; E. P. Victorova; T. A. Shakhrai; E. V. Velikanova (Новые технологии, 2020)
The article presents the results of determining the expiry date of Grushevaya food supplement obtained from the secondary resources of the processing of «Conference» pears. The use of secondary resources to obtain finished products in the form of food additives and the assessment of their consumer properties is an urgent task. One of the important consumer properties of food products is its storability along with organoleptic, physical and chemical and functional properties, as well as safety and nutritional value, which determines its shelf life,The aim of the research is to determine the shelf life of Grushevaya supplement. Changes in microbiological safety indicators during storage of Grushevaya food supplement, namely, the number of mesophilic aerobic and facultative anaerobic microorganisms (QMAFAnM), the number of molds, bacteria of Escherichia coli group (coliforms) and pathogenic microorganisms have been studied, and 18 months period has been established as its shelf life. It has been found that during the shelf life the loss of vitamin C and polyphenolic compounds in its composition is 5.5 % and 4.8 %, respectively. It has been revealed that the antioxidant activity, determined in experiments in vitro and in vivo of the food supplement after 18 months of storage differs slightly compared with those for a freshly prepared supplement.The same pattern has been established in in vivo experiments on manifestation of hepatoprotective properties in freshly prepared supplement after 18 months of storage.